2023
DOI: 10.1038/s41467-023-39476-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive mechanical/thermal response of a P(VDF-TrFE) sensor with a tailored network interconnection interface

Abstract: Ferroelectric polymers have great potential applications in mechanical/thermal sensing, but their sensitivity and detection limit are still not outstanding. We propose interface engineering to improve the charge collection in a ferroelectric poly(vinylidene fluoride-co-trifluoroethylene) copolymer (P(VDF-TrFE)) thin film via cross-linking with poly(3,4-ethylenedioxythiophene) doped with polystyrenesulfonate (PEDOT:PSS) layer. The as-fabricated P(VDF-TrFE)/PEDOT:PSS composite film exhibits an ultrasensitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Different processing conditions are used to achieve different phases of P(VDF-TrFE) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. the P-E loop study of PVDF and the copolymer is shown in Figure 5 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Piezoelectric and Ferroelectric Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Different processing conditions are used to achieve different phases of P(VDF-TrFE) [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. the P-E loop study of PVDF and the copolymer is shown in Figure 5 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Piezoelectric and Ferroelectric Polymermentioning
confidence: 99%
“…The copolymer has many advantages, such as ferroelectric phase transition, high electromechanical coupling factor, mechanical stability and spontaneous polarization. A comparative study of the dielectric constant and 𝑑 value of different polymers is listed in Table 1 and the P-E loop study of PVDF and the copolymer is shown in Figure 5 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. creating polarization.…”
Section: Piezoelectric and Ferroelectric Polymermentioning
confidence: 99%
“…Flexible conductive materials have attracted much attention for their wide applications in wearable and soft electronics, such as medical monitoring, human–computer interaction, and energy storage devices. So far, various flexible conductive materials have been developed for these applications, including conductive hydrogels, liquid metals, carbon materials, conductive polymers, and metal substrates. , Among them, conductive hydrogels, composed of a 3D polymer network and a large amount of water/solvent, are one class of the most popular candidate materials for preparing wearable and soft electronics due to their unique properties, including high stretchability, good biocompatibility, resemblance to living tissues, tunable conductivity, and softness. , In recent years, various conductive hydrogels have been developed for preparing wearable electronics and devices, such as mechanical sensors, electronic skin, and soft robotics . However, practical application of conductive hydrogels still faces challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric materials are generating significant interest for their potential use in devices that rely on the combination of spontaneous polarization that can be altered by an external electric field or stress [1][2][3][4]. Ferroelectric devices consist of ferroelectrics with a domain structure characterized by varying polarization orientations [5,6].…”
Section: Introductionmentioning
confidence: 99%